Helicobacter pylori Seropositivity and the Severity of Coronary Artery Atherosclerosis - Hassan Yousif , Salah (Diyala Journal of Medicine, 2023)
Background: A review of many kinds of literature has suggested the theory of infections to are a risk for atherosclerosis of the coronaries, many of medical researchers reported that Helicobacter pylori pathogenesis extends beyond the gastrointestinal system to be a risk factor for inflammatory-induced atherosclerosis including that of the coronary vessels. Objective: To detect a relationship between the seropositivity of Helicobacter pylori bacteria in the blood with the severity of coronary artery atherosclerosis. Patients and Methods: A total of 125 patients were taken in this study including both sex male and female with different age groups all of them admitted to cardiac center hospital in Erbil City in Iraq. Patients were suspected to have coronary artery atherosclerosis based on symptoms and primary cardiac diagnostic tools, Angiography was performed to confirm or exclude coronary artery lesions by catheterization in the cath lab of the hospital. Blood samples were taken from patients including the patients’ group and control group and a C-reactive protein (CRP) test with Helicobacter pylori IgG antibody test was done for them by using an Enzyme-linked immunosorbent assay (ELIZA) apparatus. Coronary angiography Confirmed the presence of atherosclerosis and the severity of it according to the number of vessels and the degree of luminal stenosis. Results: The results show that the most of patients with atherosclerosis (83.5%) a high level of C-reactive protein. Also, a positive significant correlation was detected between the Helicobacter pylori concentration and the number of narrowed vessels based on the results of this study Helicobacter pylori. Conclusion: According to the results Helicobacter pylori has a significant risk predictor for the severity of coronary atherosclerosis. However, evidence on this fact is not sufficient which further studies are needed.